ANALISIS KEGIATAN EKONOMI ATAS HAK CIPTA DALAM EKONOMI ISLAM - .... ...... (Program Studi Perbankan Syariah, IAIN Palopo, 2020)
Abstract: The existence of sharia provisions and protection of the Law on copyright provides adequate legal protection, of course so that the ability of intellectual rights, creativity, or community expertise can grow in line with a fair business competition climate. Copyright can be justified by Islamic Economics in terms of distributive justice. Consideration of fairness is a strong reason to support copyright. Fair that the inventor gets a reward for providing services to the community. Conversely, it would be unfair if others become